2008
DOI: 10.1007/s00405-008-0792-8
|View full text |Cite
|
Sign up to set email alerts
|

Vascular lesions of the vocal fold

Abstract: The aim of the study was to present symptoms, laryngological findings, clinical course, management modalities, and consequences of vascular lesions of vocal fold. This study examined 162 patients, the majority professional voice users, with vascular lesions regarding their presenting symptoms, laryngological findings, clinical courses and treatment results. The most common complaint was sudden hoarseness with hemorrhagic polyp. Microlaryngoscopic surgery was performed in 108 cases and the main indication of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
6
0
5
Order By: Relevance
“…Overstress results in a change of the microstructure of vocal fold mucosa [23]. Induced vessel trauma leads to hemorrhage, fibrin exudation, thrombosis and proliferation of capillaries [24]. Teleangiectatic, red-colored polyps are filled with a convolute of cavernous blood compartments with clots and can enlarge to pedunculated mobile findings [25].…”
Section: Introductionmentioning
confidence: 99%
“…Overstress results in a change of the microstructure of vocal fold mucosa [23]. Induced vessel trauma leads to hemorrhage, fibrin exudation, thrombosis and proliferation of capillaries [24]. Teleangiectatic, red-colored polyps are filled with a convolute of cavernous blood compartments with clots and can enlarge to pedunculated mobile findings [25].…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between VFH and anticoagulant use, recent upper respiratory infection (URI), and acute vocal trauma has been noted. 2,3 Some authors have proposed a correlation between hormonal imbalance and VFH based on an observed higher incidence in women. 2,4,5 However, all have stopped short of proposing a treatment strategy based on these factors.…”
Section: Introductionmentioning
confidence: 99%
“…The highest presentation was seen in professional vocalist associated with vocal abuse, this being a possible causal factor of the appearance of LV of the vocal folds. nes subyacentes (6). Estas lesiones se producen debido a la dilatación o ruptura de los vasos sanguíneos a lo largo de la cubierta mucosa de la cuerda vocal, y se caracterizan por una amplia variedad de síntomas y signos, desde fatiga vocal, disfonía, diplofonía, hasta cierre glótico incompleto (4,6).…”
Section: Introductionunclassified
“…nes subyacentes (6). Estas lesiones se producen debido a la dilatación o ruptura de los vasos sanguíneos a lo largo de la cubierta mucosa de la cuerda vocal, y se caracterizan por una amplia variedad de síntomas y signos, desde fatiga vocal, disfonía, diplofonía, hasta cierre glótico incompleto (4,6). Dentro de la fisiopatología se describe al trauma vocal agudo como gritar, llorar, tos excesiva, o puede estar asociado con el abuso crónico de la voz, el cual es visto principalmente en profesionales de la voz (6,7).…”
Section: Introductionunclassified